1993
DOI: 10.1071/mf9930437
|View full text |Cite
|
Sign up to set email alerts
|

Limnological characteristics of two coastal Dune Lakes, Jervis Bay, South Eastern Australia

Abstract: Limnological features of two permanent, closed, coastal dune lakes that are separated by only about 400 m are reported. The depth of Lake Windermere fluctuated by about 7 m during this study (1982- 1988); however, fluctuations up to 15 m were observed between 1970 and 1988. Lake Windermere is exposed to wind mixing, is transparent and is usually mixed, or only weakly stratified. Lake McKenzie is semi-perched, darkly coloured and strongly stratified with an anoxic hypolimnion during summer. It is about on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Detailed descriptions of the study site are given by Kennett and Georges (1990), Norris et al (1993) and Georges (2007, 2008). Detailed descriptions of the study site are given by Kennett and Georges (1990), Norris et al (1993) and Georges (2007, 2008).…”
Section: Study Sitementioning
confidence: 99%
“…Detailed descriptions of the study site are given by Kennett and Georges (1990), Norris et al (1993) and Georges (2007, 2008). Detailed descriptions of the study site are given by Kennett and Georges (1990), Norris et al (1993) and Georges (2007, 2008).…”
Section: Study Sitementioning
confidence: 99%
“…Although 'X. australiensis' was not reported from there by Norris et al (1993), exuviae were found by Wright & Cranston (2000) to be common in late austral summer (April) but absent in cooler September.…”
Section: Species (Names) Includedmentioning
confidence: 97%
“…The majority of lake faunal studies have reported that Chironomidae species richness in Australian lakes was very low (<12 species) (Fulton, 1983a,b; Timms, 1985; Norris et al. , 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The most common method of sampling lake benthos has involved the collection of sediment samples, usually using grab samples from the profundal zones (Fulton, 1983a,b; Timms, 1985; Norris et al. , 1993) that may miss many chironomid habitats (Franquet & Pont, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation